Animais de laboratório: O camundongo - Chorilli, Marlus [UNESP]; Michelin, D. C. [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2007)
The animal experimentation in the scientific research has contributed excessively for the development of science and technology, promoting to long of the years the discovery of prophylactic measures and treatments for diseases that attack the humans. Animals of some species have been used in the last times, being the mouse the more intensely used and more deeply known scientifically. The objective of this work was to carry through a bibliographical survey including data of our research group, about the use of mice in the animal experimentation, approaching its general biology, reproduction physiology, creation systems, genetics, habitation, feeding, handling, pain and euthanasia, techniques of risk developed in the experimentation, blood collection, pharmacological and toxicological experiments. Although current trends praise the use of alternative methods (in vitro studies, cells cultures, etc.), the animal models, as the mouse, present as main advantage the supply of information on the organism as a whole, fact that is not obtained with other methods, what still it makes possible its utilization in scientific research.

A experimentação animal nas pesquisas científicas tem contribuído sobremaneira para o desenvolvimento da ciência e tecnologia, promovendo ao longo dos anos a descoberta de medidas profiláticas e tratamentos de enfermidades que acometem os seres humanos. Animais de várias espécies têm sido utilizados nos últimos tempos, sendo os camundongos os mais intensamente utilizados e os mais profundamente conhecidos cientificamente. O objetivo deste trabalho foi realizar um levantamento bibliográfico, incluindo os trabalhos do nosso grupo, sobre o emprego de camundongos na experimentação animal, abordando sua biologia geral, fisiologia de reprodução, sistemas de criação, genética, habitação, alimentação, manejo, dor e eutanásia, técnicas de risco desenvolvidas na experimentação, coleta de sangue, experimentos farmacológicos e toxicológicos. Embora tendências atuais preconizem a utilização de métodos alternativos (estudos in vitro, culturas de células, etc.), os modelos animais, como os camundongos, apresentam como principal vantagem o fornecimento de informações sobre o organismo como um todo, fato que não é conseguido com outros métodos, o que ainda possibilita o seu emprego em pesquisas científicas. Palavras-chave: experimentação animal; camundongo; biologia geral; técnicas de risco na experimentação.
Laboratory animals: The mouse
Keywords: Animal experimentation; General biology; Mouse; Techniques of risk in the experimentation; animal euthanasia; animal experiment; animal husbandry; blood sampling; cell culture; in vitro study; medical information; medical research; mouse; mouse strain; nonhuman; pain; reproduction